2015
DOI: 10.1039/c5ra08180g
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide wrapped individual silver nanocomposites with improved stability for surface-enhanced Raman scattering

Abstract: As one of the best materials for surface-enhanced Raman scattering (SERS), Ag suffers from its tendency to oxidation, posing serious limitations for its use as a reliable long-term SERS substrate. Graphene oxide (GO) is considered to be a promising SERS-active platform due to the observed chemical enhancement originating from the interaction between probe molecules and oxygen containing functional groups on its surface. Herein, we present the synthesis of core-shell GO wrapped individual Ag nanocomposites (NCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The broad absorption peak of Ag shell was observed from the SiO 2 @PEI@Ag, likely due to the coupling between neighboring Ag nanoparticles inside the shell region, and large scattering from the SiO 2 and Ag shell. 32 Similar observation was also reported by Liu and co-workers. 12 Moreover, as the Ag shells on the SiO 2 cores became continuous and thick, the plasmon resonance peaks slightly red-shied, and the peak width became narrower.…”
Section: Resultssupporting
confidence: 84%
“…The broad absorption peak of Ag shell was observed from the SiO 2 @PEI@Ag, likely due to the coupling between neighboring Ag nanoparticles inside the shell region, and large scattering from the SiO 2 and Ag shell. 32 Similar observation was also reported by Liu and co-workers. 12 Moreover, as the Ag shells on the SiO 2 cores became continuous and thick, the plasmon resonance peaks slightly red-shied, and the peak width became narrower.…”
Section: Resultssupporting
confidence: 84%
“…Biomolecule detection [96][97][98][99][100][101][102][103][104][105], cell/tissue imaging [150,151] (standard deviation of the response (σ)/slope of the calibration curve (S))) of 100 pM. They also demonstrated that the GO-based sensing platform is feasible to detect metal ion as well as small molecules when complemented with the use of each known aptamer.…”
Section: Chemical Enhancement In Sers Induced By Electron Transfermentioning
confidence: 97%
“…In addition, the various GO-noble metal nanocomposites have been widely applied to detect extremely small amount of pigments in food, H 2 O 2 , glucose, and polar antibiotics [98][99][100][101][102][103]. In addition to its role in the enhancement of SERS signal, the combination of graphene with metal nanoparticles has been used as a favorable hybrid structure for preventing the surface oxidation of metal nanoparticles [104,105].…”
Section: Sers-based Biosensorsmentioning
confidence: 99%
“…However, the chemical enhancement of GO itself exhibits low sensitivity. To overcome this, composites that integrate the advantages of GO and high electromagnetic enhancement of gold or silver nanoparticles (Au or Ag NPs) have been developed for SERS detection [39,40,41,42,43,44,45,46]. Metal NPs were deposited on the surface of GO via oxygen-containing functional groups, such as carbonyl and hydroxyl groups [47,48].…”
Section: Introductionmentioning
confidence: 99%